2022
DOI: 10.3390/metabo12100959
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gestational Diabetes Mellitus on Cholesterol Metabolism in Women with High-Risk Pregnancies: Possible Implications for Neonatal Outcome

Abstract: Metabolic disorders in pregnancy, particularly gestational diabetes mellitus (GDM), are associated with an increased risk for adverse pregnancy outcome and long-term cardiometabolic health of mother and child. This study analyzed changes of serum cholesterol synthesis and absorption markers during the course of high-risk pregnancies, with respect to the development of GDM. Possible associations of maternal lipid biomarkers with neonatal characteristics were also investigated. The study included 63 women with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Circulatory endogenous precursors of cholesterol can be used as markers of cholesterol synthesis, while phytosterols, which use the same absorption route as cholesterol, are proposed as cholesterol absorption markers (Figure 4) [122]. Cholesterol synthesis and absorption are reciprocally regulated in healthy individuals, but it has been demonstrated that various pathological states are characterized by the disturbance of the balance between these processes [123][124][125][126][127][128][129][130]. Accordingly, non-cholesterol sterols could be used, not only as indicators of altered cholesterol homeostasis, but also as markers of several diseases, including CVD, and predictors of therapeutic response.…”
Section: Biomarkers Of Oxidative Stress and Atherogenic Dyslipidemia:...mentioning
confidence: 99%
“…Circulatory endogenous precursors of cholesterol can be used as markers of cholesterol synthesis, while phytosterols, which use the same absorption route as cholesterol, are proposed as cholesterol absorption markers (Figure 4) [122]. Cholesterol synthesis and absorption are reciprocally regulated in healthy individuals, but it has been demonstrated that various pathological states are characterized by the disturbance of the balance between these processes [123][124][125][126][127][128][129][130]. Accordingly, non-cholesterol sterols could be used, not only as indicators of altered cholesterol homeostasis, but also as markers of several diseases, including CVD, and predictors of therapeutic response.…”
Section: Biomarkers Of Oxidative Stress and Atherogenic Dyslipidemia:...mentioning
confidence: 99%
“…Dyslipidemia in pregnancy is associated with gestational diabetes mellitus (GDM), preeclampsia, macrosomia, preterm birth, and other pregnancy complications. Women with a rich-in-cholesterol diet have a higher incidence of developing gestational diabetes (15). A low level of HDL-C and an elevated BMI have a particular impact on the development of GDM (13).…”
Section: The Impact Of Dyslipidemia On Pregnancymentioning
confidence: 99%